Numerical investigations about the sound transmission loss of a fuselage panel section with embedded periodic foams. (November 2021) - Magliacano, Dario; Petrone, Giuseppe; Franco, Francesco; De Rosa, Sergio
Abstract: The scope of this paper is to investigate the sound transmission loss of a typical fuselage panel section, as well as to propose solutions based on the inclusion of a periodic pattern inside its foam core, which aim at passively improving the acoustic performance in a mid-high range of frequencies. In detail, a new fuselage panel configuration is numerically studied, starting from the state of the art regarding the acoustic packages based on porous meta-materials. The main novelties of the present work are represented by the application of a meta-core solution inside an acoustic package of aeronautical interest, as well as a systematic investigation of the effects deriving from its geometrical parameters. In order to reach this goal, a numerical model of a fuselage panel section is studied, and the effect of several periodic patterns are simulated; more specifically, twelve configurations are taken into account, each with different radius of the inclusions and number of unit cells along the thickness. For each of these layouts, the mass increase of the so-called meta-core, compared to that of its classical homogeneous counterpart, is estimated, together with the associated mid-band frequency and amplitude of the sound transmission loss peak, which is caused by the additional acoustic modes excited by the periodic nature of the meta-core itself. Results are presented in terms of tables and graphs, which may constitute a good basis in order to perform preliminary design considerations that could be interesting for further generalizations.